Effectiveness of the Incredible Years Parenting Program for Families with Socioeconomically Disadvantaged and Ethnic Minority Backgrounds. Issue 1 (2nd January 2017) - Leijten, Patty; Raaijmakers, Maartje A. J.; Orobio de Castro, Bram; van den Ban, Els; Matthys, Walter
Abstract : Families with socioeconomically disadvantaged and ethnic minority backgrounds are often hard to reach for the prevention and treatment of disruptive child behavior problems. We examined whether the Incredible Years parenting intervention can successfully reach and benefit families with socioeconomic disadvantaged and ethnic minority backgrounds in the Netherlands. One hundred fifty-four families from a wide range of socioeconomic and ethnic backgrounds were recruited in an outpatient clinic for child and adolescent psychiatry and in elementary schools serving deprived neighborhoods. Families were randomly assigned to the BASIC Incredible Years parenting intervention or a waiting list control condition. Children were 3–8 years old ( M = 5.59, SD = 1.35; 62% boys, 66% ethnic minorities) and 65% of the children met Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev.) criteria for oppositional defiant disorder, conduct disorder, and/or attention-deficit hyperactivity disorder. Incredible Years reduced parent-reported disruptive child behavior and teacher-reported hyperactive and inattentive child behavior and increased parent-reported use of praise and incentives and reduced harsh and inconsistent discipline. Incredible Years did not affect parent-reported hyperactive and inattentive child behavior; teacher-reported child conduct problems; and parent-reported use of appropriate discipline techniques, clear expectations, physical punishment, and parenting stress. Of importance, the effectiveness of Incredible Years did not differ across families with different socioeconomic and ethnic backgrounds. Effects were maintained at 3-month follow-up. This study shows that socioeconomically disadvantaged and ethnic minority families in disadvantaged neighborhoods can be engaged in and benefit from parenting interventions to reduce disruptive child behavior.